Analisis Kestabilan Titik Tetap Model Matematika Penyebaran Penyakit DBD Tipe SEIR - Elinora Naikteas Bano (Fakultas Pertanian, Universitas Timor, 2018)
Dengue is one of the infectious diseases transmitted to humans by the bite of Aedes aegypti or Aedes albopictus mosquitoes. Dengue virus infections include dengue fever, dengue hemorrhagic fever and Dengue Shock Syndrome (DSS). The dengue virus has four types of serotypes: DEN_1, DEN_2, DEN_3, DEN_4. In the model, will be studied the dynamics of the spread of dengue hemorrhagic disease type SEIR. From the model then fixed point will be determined, then analyzed the stability of each fixed point by considering the basic reproduction number (R_0 ). The results showed that for fixed point without disease the condition would be stable when R_0<1, while the fixed point of endemic would be stable for condition whenR_0>1.